THE SAFETY OF GLUCOCORTICOIDS IN THE TREATMENT OF INFAMMATORY RHEUMATIC DISEASE : A SYSTEMATIC REVIEW - Rossiyah, Nella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Glucocorticoids have been utilized as a component of the treatment for rheumatoid arthritis ever since their introduction some decades ago. It has been established that glucocorticoids are effective in lowering the inflammatory activity induced by this condition and in slowing the course of erosive joint degradation. Both of these benefits can be attained by taking the medication. Unfortunately, they also have a wide variety of potentially adverse consequences, the severity of which may vary depending on the dosage and the length of the therapy. Nevertheless, the benefits of these medications far outweigh the risks associated with them. As a result of the rise in popularity of many alternative therapy alternatives, the use of glucocorticoids as a treatment method is currently being debated (such as biologic and targeted synthetic disease-modifying antirheumatic medicines). It is possible to provide corticosteroids by injecting them directly into the joint. Many people are opposed to the use of glucocorticoids because of the dose-dependent adverse effects that they can have, despite the fact that they continue to be an essential component in the treatment of a wide variety of inflammatory rheumatic diseases. The usage of glucocorticoids for an extended period of time is connected with a greater risk of experiencing adverse consequences. These problems are associated with an increased chance of developing cardiovascular disease, diabetes, and possibly mortality.